The populist rhetoric as a threat to human rights in Europe: stance of the supranational institutions. - Avilés-Hernández, Elena (Universidad de Deusto, 2019)
The populist rhetoric taken place in Europe not long ago has only accentuated the social divisions and segregation of certain minority groups who saw their rights violated in favour of a new concept of security. The main victims of this situation are foreigners and ethnic minorities, groups perceived as a threat to social cohesion and order; a perception radicalised through the media and social networks. This situation is part of a context of growing tensions, religious extremism and violent radicalism used, in some cases, by the government elite itself to support legislative changes or justify arbitrary interventions. The result is a restriction of fundamental rights legitimized by governments themselves.
La retórica populista como amenaza a los derechos humanos en Europa: Posicionamiento de las instituciones supranacionales
Keywords: Derechos humanos - Países de la Unión Europea; Retórica - Aspectos políticos; Human Rights; Migration; Terrorism; Nationalism; ECtHR